Assessing Online Homework in First-Semester Calculus. Issue 6 (2nd July 2016) - Callahan, Jason T.
Abstract: This paper describes and assesses the implementation of online homework in a first-semester calculus course. Comparing sections of the course before implementation to those after, we find statistically significant improvements in retention rates, measures of student engagement, and participation on homework. We do not, however, find statistically significant changes in the proportions of students passing the common final exam or earning a C grade or better for the course. We conclude with a discussion of qualitative aspects and implications of our implementation of online homework.